2021
DOI: 10.3168/jds.2020-19155
|View full text |Cite
|
Sign up to set email alerts
|

Heifers with positive genetic merit for fertility traits reach puberty earlier and have a greater pregnancy rate than heifers with negative genetic merit for fertility traits

Abstract: This study investigated the hypothesis that dairy heifers divergent in genetic merit for fertility traits differ in the age of puberty and reproductive performance. New Zealand's fertility breeding value (FertBV) is the proportion of a sire's daughters expected to calve in the first 42 d of the seasonal calving period. We used the New Zealand national dairy database to identify and select Holstein-Friesian dams with either positive (POS, +5 FertBV, n = 1,334) or negative FertBV (NEG, −5% FertBV, n = 1,662) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…The New Zealand Fertility Breeding Value (FertBV) was used to create cows with positive (POS; +5%) or negative (NEG; −5%) genetic merit for fertility traits. At the same time, limits were put on the inbreeding coefficient of the offspring (<12%) and the expected parent averages for milk volume, fat, protein, BW, and ancestry (% North American Holstein-Friesian) to ensure groups were within 1 standard deviation and calves were >15/16 parts Holstein-Friesian as described in Meier et al (2021a). These calves were followed for over 3 yr to determine influences of the FertBV on puberty (Meier et al, 2021a) and other reproductive phenotypes (Meier et al, 2021b; Figure 1).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The New Zealand Fertility Breeding Value (FertBV) was used to create cows with positive (POS; +5%) or negative (NEG; −5%) genetic merit for fertility traits. At the same time, limits were put on the inbreeding coefficient of the offspring (<12%) and the expected parent averages for milk volume, fat, protein, BW, and ancestry (% North American Holstein-Friesian) to ensure groups were within 1 standard deviation and calves were >15/16 parts Holstein-Friesian as described in Meier et al (2021a). These calves were followed for over 3 yr to determine influences of the FertBV on puberty (Meier et al, 2021a) and other reproductive phenotypes (Meier et al, 2021b; Figure 1).…”
Section: Animalsmentioning
confidence: 99%
“…Full details of the heifer breeding are described in Meier et al, (2021a). In brief, weekly plasma sampling for progesterone analysis started when heifers were approximately 190 kg and continued until puberty was reached.…”
Section: Reproductive Management Of the Heifersmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative model was recently established by Meier et al (2021a,b) using a 500-cow study population divergent in genetic merit for fertility traits based on the New Zealand fertility breeding value (FertBV). The goal was to establish an animal model only divergent in FertBV, by limiting differences in breeding values for BCS, BW, and milk production traits (Meier et al, 2021b). Approximately half the study cows were custom bred to be positive (+5%; POS) and half negative (−5%; NEG) for FertBV.…”
Section: Introductionmentioning
confidence: 99%
“…Greater circulating concentrations of aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT) have also been reported in cows that had not ovulated by 3 wk postcalving compared with those that had (Kawashima et al, 2016), supporting an important role of liver function in the resumption of estrous. Our studies involved cows that differed in their FertBV as indicated minor BCS differences over the transition period, but there was a wide range of PPAI, especially in NEG cows (Meier et al, 2021b). Therefore, we hypothesized that blood metabolite, minerals and metabolic stress marker profiles during the transition period would be similar among the POS and NEG cows, but may be associated with duration of PPAI.…”
Section: Introductionmentioning
confidence: 99%